Tinjauan Kriminologi dan Upaya Penegakan Hukum Tindak Pidana Kekerasan Seksual terhadap Perempuan di Derah Istimewa Yogyakarta (Studi di Kepolisian DIY) - Amalia Warahafida; Ayu Izza Elvany (Prosiding Seminar Hukum Aktual Fakultas Hukum Universitas Islam Indonesia, 2024)
The increase in cases in 2022-2024 in Yogyakarta has obstacles in the law enforcement process and high cases of sexual violence. This research examines the criminological review and law enforcement efforts of Sexual Violence Crime (TPKS) against women in the Special Region of Yogyakarta, to find out the factors that cause TPKS to occur in the Yogyakarta Special Police area and the efforts of the Yogyakarta Special Police in enforcing the law of TPKS against women in the Special Region of Yogyakarta. The research method used in this research is empirical legal research. The research approach used is a sociological approach. Based on the results of the research conducted, first, the factors causing the occurrence of TPKS against women in the Yogyakarta Special Police Region are psychological factors and are in accordance with the theory of differential association. Second, law enforcement efforts carried out by the Yogyakarta Special Region Police are preemptive, preventive, and repressive. However, it is necessary to evaluate preemptive and preventive programs and increase repressive efforts.